Cerebral motor control in patients with gliomas around the central sulcus studied with spatially filtered magnetoencephalography. Issue 3 (13th February 2004) - Taniguchi, M; Kato, A; Ninomiya, H; Hirata, M; Cheyne, D; Robinson, S E; Maruno, M; Saitoh, Y; Kishima, H; Yoshimine, T
Abstract : Objective: Application of spatially filtered magnetoencephalography (MEG) to investigate changes in the mechanism of cerebral motor control in patients with tumours around the central sulcus. Methods: MEG records were made during a repetitive hand grasping task in six patients with gliomas around the central sulcus and in four control subjects. Power decreases in the α (8–13 Hz), β (13–30 Hz), and low γ bands (30–50 Hz) during the motor tasks (event related desynchronisation, ERD) were analysed statistically with synthetic aperture magnetometry. The tomography of ERD was superimposed on the individual's magnetic resonance image. Results: β ERD was consistently localised to the contralateral primary sensorimotor cortex (MI/SI) in control subjects, whereas the α and low γ ERD showed considerable intersubject variability. β ERD in patients during non-affected side hand movement was also localised to the contralateral MI/SI, but exclusively to the ipsilateral hemisphere during affected side hand movement. Conclusions: The altered pattern of ERD in the patient group during affected side hand movement suggests recruitment of diverse motor areas, especially the ipsilateral MI/SI, which may be required for the effective movement of the affected hand.